The Effect of Music Therapy on Pain The Level of Postoperative Patients' with Caesarean Section at Islamic Hospital A.Yani, Surabaya - Handayani, Nanik (Unusa Press, 2012)
Pain is the most common effects in patients after undergoing surgery of Caesarean section. Pain management using pharmacological and non pharmacological management, one of non-pharmacological management is using music therapy The purpose of this study was to analyze the effect of music therapy on pain level of postoperative patients' with Caesarean section. The type of study is analytic with True Experimental type with Pre Post Test Control Group Design done by Random Allocation. The study population is post-operative Caesarean section mothers who are hospitalized in Surabaya Islamic Hospital Surabaya Jl. A Yani since May 2011. The Sample are some populations above mentioned with amount of 24 respondents, 12 respondents as a control and 12 respondents were given music therapy. The Sampling technique uses Consecutive Sampling. Independent variable is music therapy and dependent variable is pain level. The instrument used to measure the independent variables is a check sheet lists while the dependent variable is Descriptive Pain Intensity Scale. To analyze the changes of pain level in the control group and the treatment used Paired T Test, the result showed that values of ρ is 0.166 or (ρ > 0.05), so there is no significant change of pain level on a pre test and post test control group, whereas in treatment group obtained value of ρ is 0.000 or (ρ < 0.05), so there is a significant change of pain level on a pre test and post test. To analyze differences of pain levels in control group and treatment group is used Independent T Test. The results of study got value of ρ is 0.807 (ρ > 0.05). So there is no significant difference of pain level pre test in control and treatment groups, while the post test value of ρ is 0.024 (ρ < 0.05). So there is a significant difference of pain level post test in control and treatment groups. So it can be conclude that there is influence of music therapy toward pain levels of postoperative patients of Caesarean section. Music therapy is expected to be used as a Complementary Therapy to reduce pain at the incision Caesarean section.